Penggunaan Antibiotik Pada Pasien Pneumonia Covid-19: Studi Kuantitatif Pada Rumah Sakit Dr. R. Goeteng Taroenadibrata Purbalingga - Suseno, Akhmad Haris; Kusuma, Anjar Mahardian; Galistiani, Githa Fungie; Harima, Gangga (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2024)
Covid-19 is a problem for the world and Indonesia. Pneumonia is one of the most common comorbid diseases of Covid-19. The management of Covid-19 pneumonia is using empirical antibiotics. Inappropriate use of antibiotics can lead to antibiotic resistance so it is very necessary to evaluate the use of antibiotics. The purpose of this study was to determine the quantity of antibiotic use in patients with Covid-19 pneumonia at Dr. R. Goeteng Taroenadibrata Purbalingga Hospital. This study used a cross sectional research design using retrospective data with observational research. The method of evaluating antibiotic use uses the ATC/DDD methods. Based on the evaluation using the ATC/DDD method, The DDD/100 patient-days value of antibiotic use was intravenous Azithromicin (52,860 DDD/100 patient-days), Ceftriaxone (42,412 DDD/100 patient-days), peroral Azithromicin (8,582 DDD/100 patient-days), Levofloxacin (6,529 DDD/100 patient-days), Cefixime (2,985 DDD/100 patient-days), Ciprofloxacin (1,243 DDD/100 patient-days), Cefotaxime (2,798 DDD/100 patient-days) and Metronidazole (1,119 DDD/100 patient-days). There are 2 types of antibiotics that meet WHO standards and 6 types of antibiotics that do not meet WHO standards.